2017
DOI: 10.4172/2576-3881.1000118
|View full text |Cite
|
Sign up to set email alerts
|

Soluble TNF Receptors are Modulated by Vitamin D Status but not by Acute Perturbations in 25-Hydroxyvitamin D Following A Bolus of Supplemental Vitamin D

Abstract: The first objective of this study was to identify if soluble tumor necrosis factor-receptor 1 (sTNFr1) and -receptor 2 (sTNFr2) are modulated by vitamin D status (insufficient vs. sufficient). The second objective was to reveal if soluble TNF receptors fluctuate with serum 25-hydroxyvitamin D (25(OH)D) concentrations following a bolus of supplemental vitamin D. Reportedly healthy male adults were randomly (double-blind) assigned to a placebo (n=15) or vitamin D (100,000 IU of cholecalciferol; n=14) supplement.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 55 publications
(40 reference statements)
0
5
0
Order By: Relevance
“…Tyler Barker et al determined/assessed serum TNFR and vitamin D association in a randomized clinical trial (RCT) including vitamin D deficient, insufficient, and sufficient subjects in both the placebo and treatment groups. In that study, vitamin D supplementation (one bolus) in apparently healthy men was done with a dose of 100,000 IU [30]. At the end of the study, the results showed that in healthy male adults, supplementation of vitamin D could lead to decreases in the sTNFr2 level; however, there was no change in serum TNF-α.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Tyler Barker et al determined/assessed serum TNFR and vitamin D association in a randomized clinical trial (RCT) including vitamin D deficient, insufficient, and sufficient subjects in both the placebo and treatment groups. In that study, vitamin D supplementation (one bolus) in apparently healthy men was done with a dose of 100,000 IU [30]. At the end of the study, the results showed that in healthy male adults, supplementation of vitamin D could lead to decreases in the sTNFr2 level; however, there was no change in serum TNF-α.…”
Section: Discussionmentioning
confidence: 99%
“…At the end of the study, the results showed that in healthy male adults, supplementation of vitamin D could lead to decreases in the sTNFr2 level; however, there was no change in serum TNF-α. Also, the data suggested that soluble TNF receptors could be modulated in vitamin D sufficient, insufficient, or deficient subjects [30].…”
Section: Discussionmentioning
confidence: 99%
“…In addition to protecting against the reduction in postoperative 25(OH) concentrations, we also demonstrate that there was arguably an early plateau in plasma 25(OH)D concentrations from postoperative day 3 to discharge in the vitamin D group. Prior studies identify a continuous rise in serum 25(OH)D concentrations 7 to 14 days after a single bolus of cholecalciferol at 50,000 or 100,000 IU (Armas et al, 2004; Barker et al, 2017; Heaney et al, 2008; Ilahi et al, 2008). Although those findings were reported in healthy Participants (Armas et al, 2004; Barker et al, 2017; Heaney et al, 2008; Ilahi et al, 2008), we anticipated a continuous increase in plasma 25(OH)D following cholecalciferol supplementation and prior to hospital discharge in open‐heart surgery patients.…”
Section: Discussionmentioning
confidence: 99%
“…Prior studies identify a continuous rise in serum 25(OH)D concentrations 7 to 14 days after a single bolus of cholecalciferol at 50,000 or 100,000 IU (Armas et al, 2004; Barker et al, 2017; Heaney et al, 2008; Ilahi et al, 2008). Although those findings were reported in healthy Participants (Armas et al, 2004; Barker et al, 2017; Heaney et al, 2008; Ilahi et al, 2008), we anticipated a continuous increase in plasma 25(OH)D following cholecalciferol supplementation and prior to hospital discharge in open‐heart surgery patients. This study, however, challenges this assumption and provides original data suggesting that plasma 25(OH)D concentrations reach and maintain their zenith 3 days after open‐heart surgery and only 24 hours after the last of three loading doses (50,000 IU of cholecalciferol each) of supplemental vitamin D over 4 days.…”
Section: Discussionmentioning
confidence: 99%
“…Serum cytokine concentrations were measured in four groups of subjects ( n = 218): (1) reportedly-healthy and non-injured control subjects (CON; n = 92; ≥ 18 years), (2) subjects scheduled to undergo primary, unilateral anterior cruciate ligament surgery (ACL; n = 42; 18–45 years), (3) non-surgical subjects with unilateral knee osteoarthritis (OA; n = 60; 18–60 years), and (4) subjects with end-stage knee osteoarthritis scheduled to undergo a primary, unilateral total knee arthroplasty (TKA; n = 24; ≥ 18 years). Baseline (i.e., prior to intervention in previous studies, where applicable) data from some of the CON 30 , 31 , ACL 9 , 32 , and OA 33 , 34 subjects have been previously published. All subjects were informed of and provided written and verbal consent to the study protocols and procedures.…”
Section: Methodsmentioning
confidence: 99%